An Environmental Scan of Academic Emergency Medicine at the 17 Canadian Medical Schools: Why Does this Matter to Emergency Physicians?. Issue 1 (21st July 2016) - Stiell, Ian G.; Artz, Jennifer D.; Lang, Eddy S.; Sherbino, Jonathan; Morrison, Laurie J.; Christenson, James; Perry, Jeffrey J.; Topping, Claude; Woods, Robert; Green, Robert S.; Lim, Rodrick; Magee, Kirk; et al.
Abstract: Objective: We sought to conduct a major objective of the CAEP Academic Section, an environmental scan of the academic emergency medicine programs across the 17 Canadian medical schools. Methods: We developed an 84-question questionnaire, which was distributed to academic heads. The responses were validated by phone by the lead author to ensure that the questions were answered completely and consistently. Details of pediatric emergency medicine units were excluded from the scan. Results: At eight of 17 universities, emergency medicine has full departmental status and at two it has no official academic status. Canadian academic emergency medicine is practiced at 46 major teaching hospitals and 13 specialized pediatric hospitals. Another 69 Canadian hospital EDs regularly take clinical clerks and emergency medicine residents. There are 31 full professors of emergency medicine in Canada. Teaching programs are strong with clerkships offered at 16/17 universities, CCFP(EM) programs at 17/17, and RCPSC residency programs at 14/17. Fourteen sites have at least one physician with a Master's degree in education. There are 55 clinical researchers with salary support at 13 universities. Sixteen sites have published peer-reviewed papers in the past five years, ranging from four to 235 per site. Annual budgets range from 200, 000 to 5, 900, 000. Conclusion: This comprehensive review of academic activities in emergency medicine across Canada identifies areas of strengths as well as opportunities for improvement. CAEP and the Academic Section hope we can ultimately improve ED patient care by sharing best academic practices and becoming better teachers, educators, and researchers. RÉSUMÉ: Objectif: Les auteurs cherchaient à atteindre un objectif important que s'était fixé la section des affaires universitaires de l'ACMU, soit l'analyse environnementale des programmes de médecine d'urgence universitaire, offerts dans les 17 écoles de médecine au Canada. Méthode: Les auteurs ont élaboré un instrument d'enquête composé de 84 questions, qui a été envoyé aux responsables de service. Les réponses ont été validées au téléphone par l'auteur principal afin de s'assurer de leur cohérence et de leur caractère complet. Toutefois, les renseignements concernant les services de médecine d'urgence pédiatrique n'ont pas été inclus dans l'analyse. Résultats: La médecine d'urgence est reconnue comme département à part entière dans 8 universités sur 17, tandis qu'elle ne jouit d'aucun titre officiel dans 2 autres universités. Des programmes de médecine d'urgence universitaire au Canada sont offerts dans 46 grands hôpitaux d'enseignement et dans 13 hôpitaux d'enseignement spécialisés en pédiatrie. Dans 69 autres hôpitaux, les services des urgences acceptent habituellement des stagiaires cliniques et des résidents en médecine d'urgence. Il y a 31 professeurs titulaires de médecine d'urgence au Canada. Les programmes d'enseignement sont présents dans de nombreux établissements : ainsi, des stages cliniques sont offerts dans 16 universités sur 17; les programmes de CCMF(MU), dans 17 universités sur 17; et les programmes de résidence du CRMCC, dans 14 universités sur 17. On compte au moins 1 médecin ayant une maîtrise en éducation dans 14 services et 55 cliniciens-chercheurs recevant une aide salariale dans 13 universités. Des articles évalués par les pairs ont été publiés dans 16 services au cours des 5 dernières années, et le nombre varie de 4 à 235 dans chacun d'eux. Enfin, les budgets annuels vont de 200 000 à 5 900 000 . Conclusion: Cet examen global des activités universitaires en médecine d'urgence menée à la grandeur du pays permet de cerner les points forts ainsi que les points susceptibles d'amélioration. L'ACMU et la section des affaires universitaires souhaitent, en fin de compte, une amélioration des soins donnés aux patients dans les SU, et ce, par la mise en commun de pratiques exemplaires dans les universités et par la formation de meilleurs enseignants, de meilleurs moniteurs et de meilleurs chercheurs.